Poučevanje težavnih študentov: 10. učna delavnica za mentorje družinske medicine: zbornik predavanj (University of Maribor Press, 2022)
Teaching Difficult Students: 10th Learning Workshop for Family Medicine Mentors: Proceedings. Steinert identified as ’difficult’ students those who fail to meet the expectations of the educational program. Usually, such students require more supervision, more time, which means less time for patients. In this case, mentors and teachers need additional knowledge and pedagogical skills. Much has been written about difficult patients, and slightly fewer records are found about difficult students, especially when looking for definitions among medical articles. One definition states: “Difficult students are persistently disruptive, like to defy instructions, demand attention, or are completely unmotivated to work. They are students who ignore authority and cause teachers stress, frustration and anger. ”Teaching difficult students is a challenge for both teachers and students. In the present collection, we have described some tools that can help us with this. Students as well as future family medicine doctors and mentors shared their experiences with teaching in the field of Family Medicine and education.